Preparation, Characterization and Antibacterial Activity of Poly(epsilon-caprolactone) Electrospun Fibers Loaded with Amoxicillin for Controlled Release in Biomedical Applications - Malagon Aviles, O. (2012)
Amoxicillin (AMOX) was successfully encapsulated at different concentrations into poly(caprolactone) (PCL) by the electrospinning technique, and mats of non-woven fibers were obtained and characterized in terms of morphology, in vitro release and antibacterial properties. The scanning electron microscopy evidenced the nanofibrous structure of the pristine PCL, composed of individual, uniform, and randomly oriented fibres with an average diameter ranging around 0.8 micron. The addition of amoxicillin at different concentrations (3, 5 and 7) did not evidence change in the fiber morphology. The release curves, for all samples, present mainly two stages: a first stage, quick as a burst, is followed by a second slow stage. The burst was analyzed as a function of amoxicillin concentration and thickness of the membranes, and values corresponding to absence of burst were individuated. In the second stage the release was found very slow extending up to months for the most concentrated sample. The antibacterial activity of the electrospun fibers was effective to inhibit in different proportions Staphylococcus aureus, Enterococcus faecalis and Escherichia coli. The properties of the filled membranes and their capability for local delivery of antibiotics make them suitable for biomedical applications.